SPIRITUAL DEVELOPMENT OF HUMANITY FOR LEAPING INTO A NEW LIFE - Kesornpatumanunt, Sirilux; Sitthikul, Supreeya; Tongchai, Prawit; Panthong, Kanok (Academic Journal of Thailand National Sports University, 2019)
This qualitative research aims to study the processes of spiritual development of humanity for leaping into a new life and the perspectives of persons who passed the processes. Key Informants are Professor Sathittham Pensuk and the 17 persons who were trained more than 1 month in the course of spiritual development. In-depth interview and participant observation were conducted for data collection. The results revealed that the process of spinitual development of humanity for leaping into a new life is to perform spiritual-quake in order to get rid of futile thinking and promote a feeling of awareness by using various activities. There are 3 steps as following: Step 1, Mind Preparing before Coaching; Step 2, Power of Mind Coaching, Personal Coaching and Coaching by Group Process; and Step 3, Self-Coaching. Each step started by channeling between Professor Sathittham Pensuk and participants to select coaching methods or activities and create an atmosphere through appropriate sound waves and light waves together with setting new spiritual programs, called Rebirth Coaching. The persons who passed the processesgavemany perspectivesof their lifechangingas follows.1) Physical Aspect found a healthier. 2) Mental Aspect found a more mental health and a positive attitude in way of life, which brings about good personalities and leads to good relations to society and other persons. 3) Intelligence Aspect found a quicker learning, an easier life understanding and a better problem handling. And 4) Miracle of life Aspect found an unbelievable good experiences and an automatic spiritual experiences. This study shows that the processes can lead to changing in a better way of life. Therefore, the processes can be used as a guideline to practice spiritual development in order to be a perfect human. In addition, it should be another way to try to exercise psychological fitness, which is a component of sports success